Probable brown dwarf companions detected in binary microlensing events during the 2018-2020 seasons of the KMTNet survey - Han, Cheongho; Jung, Youn Kil; Kim, Doeon; Gould, Andrew; Bozza, Valerio; Bond, Ian A.; Chung, Sun-Ju; Albrow, Michael D.; Hwang, Kyu-Ha; Ryu, Yoon-Hyun; Shin, In-Gu; Shvartzvald, Yossi; et al. (Astronomy and astrophysics, 2023)
Aims: We inspect the microlensing data of the KMTNet survey collected during the 2018-2020 seasons in order to find lensing events produced by binaries with brown dwarf (BD) companions. Methods: In order to pick out binary-lens events with candidate BD lens companions, we conducted systematic analyses of all anomalous lensing events observed during the seasons from 2018 to 2020. By applying a selection criterion of mass ratio between the lens components of 0.03 ≲ q ≲ 0.1, we identify four binary-lens events with candidate BD companions, namely KMT-2018-BLG-0321, KMT-2018-BLG-0885, KMT-2019-BLG-0297, and KMT-2019-BLG-0335. For the individual events, we present interpretations of the lens systems and measure the observables that can be used to constrain the physical lens parameters. Results: The masses of the lens companions estimated from the Bayesian analyses based on the measured observables indicate high probabilities that the lens companions are in the BD mass regime; that is, 59%, 68%, 66%, and 66% for the four respective events.